FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI LANSIA PADA POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS II DENPASAR SELATAN : ANALISIS JALUR - Pratiwi, Ni Made Vidya; Widarsa, Ketut Tangking; Kurniasari, Ni Made Dian (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p01, 2022)
ABSTRACT The participation of the elderly in the work area of the South Denpasar Health Center II is still far below the target. This study aims to determine the factors that influence participation of elderly in Posyandu of the elderly in the work area of South Denpasar Health Center II. A cross-sectional study was conducted on 120 elderly who were selected from 6 Posyandu in working area of South Denpasar Health Center II. Data about support of cadres, health workers, families, the knowledge and attitudes of the elderly were collected by interview, level of elderly participation is measured by the number of attendance recorded at the Posyandu registers. Data were analyzed by path analysis method with a significance level of 0.05. The results showed that cadre support did not affect the participation, knowledge and attitudes of the elderly (p> 0.05). The support of health workers has indirect effect on increasing knowledge and attitudes with loading factors of 0.09 and 0.27, respectively. Family support has direct and indirect effects through knowledge and attitudes with a total effect of 0.127 (p <0.05). Knowledge directly and indirectly influences participation through attitude with a total effect of 0.785 (p <0.05). It was concluded that cadre support had no effect on the participation of the elderly, whereas family and health staff support had an influence through increasing the knowledge of the elderly. Therefore family support and health workers should be optimized. Keywords: Elderly, Elderly Posyandu, Participation